Pengaruh Geometri Gerigi dan Kecepatan Putar Terhadap Kinerja Mesin Parut Sagu Tipe Silinder - Darma Darma; Reniana Reniana; Budi Santoso; Jhonson Waromi (The University of Lampung, 2021)
Sago rasping machine or sago rasper is the most commonly used in sago processing both for small and large scale. It function is to reduce the size or to disintegrate sago pith into smaller particle. By doing so, the starch contained in the pith can be separated in the subsequent process. The amount of starch resulted depend on the size of rasped pith. The smaller the pith is rasped the higher the starch can be extracted. The purpose of this research was to test the effect of teeth geometrical shape and cylinder rotation speed on performance of sago rasping machine. There are four type of teeth geometrical shape namely cylinder, pyramid, screw, and cube and three levels of cylinder rotation speed they are 1500 rpm, 2000 rpm and 2500 rpm were tested. Results showed that the rasping capacity was affected significantly by the two single factors as well as its interaction of teeth geometrical shape and cylinder rotation speed. Similarly, starch yield and starch losses in waste were significantly affected by teeth geometrical shape. Meanwhile, starch yield and starch losses in waste were not affected significantly by cylinder rotation speed and the interaction of the two factors. The best performance was resulted at the treatment of teeth geometrical shape of screw with the speed of cylinder rotation 2500 rpm. The performances at the treatment were: (a) rasping capacity was 918 kg/h, (b) starch yield was 48%, (wb), (c) starch loss in waste was15.1%.Keywords: cylinder type, rasping performance, sago rasping machine, teeth geometry